Growing in the Womb: The Effect of Seismic Activity on Fetal Growth - Romero, J; Chirkova, S (Elsevier B.V., 2020)
We study whether exposure to earthquake affects health at birth. A mother-fixed-effect model together with the spatiotemporal variation of earthquakes in Chile allow us to better estimate the impacts on birth outcomes. Our findings show that exposure to earthquakes affects fetal growth. Infants born to mothers exposed to earthquakes in the second trimester are 1.8% more likely to be large for gestational age (LGA), which is a large effect from a baseline of 7% of LGA newborns. The reported impact varies across mothers’ socioeconomic status, with relatively poorer Chilean mothers being more vulnerable to earthquakes. A possible mechanism that explains these results could work through changes in the incidence of women with diabetes. We provide indirect evidence in this regard. Mothers with diabetes are more likely to have large-for-gestational-age babies. Exposure to earthquakes increases the incidence of diabetes among the affected population, with the observed impact on diabetes being relatively higher among women of lower socioeconomic status. © 2019 Elsevier B.V.